Challenges facing a Nicaraguan producer operating in the agricultural market (regional and local) and alternative methods of solving them. Part 1 - Montiel Silva, Manuel Ernesto (Przegląd Prawa Rolnego, 2018)
The aim of the article is to present the regulation of the Nicaraguan agricultural market and to identify legal solutions that could contribute to overcoming the unequal distribution of economic resources resulting from domestic agricultural activity in the food supply chain. In particular, the aim is to identify the legal loopholes that contribute to the unequal distribution of resources in the Nicaraguan agri-food supply system and to propose alternative solutions that are available from the point of view of agricultural law science. In the author’s opinion, the main difficulty facing the Nicaraguan agricultural producer is the commercialisation of own goods on the agricultural products market of Central America and Nicaragua and the regulatory deficiencies in this respect. The System of Central American Integration (Sistema de la Integración Centroamericana – SICA) in force in most countries of the region, includes on the one hand comprehensive legal regulations concerning agriculture, but on the other hand it does not fully correspond to the modern structure of the agri-food chain. In practice, regional and national legislation is subject to frequent amendments and provides unsatisfactory protection for agricultural producers at every stage of production. The introduction of changes at the regional level in the form of free economic circulation zones and the implementation of the common agricultural policy by Central American countries offers a certain alternative to this situation.